2021
DOI: 10.3389/fpsyg.2021.745295
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Learning Design for Technology Education: A Soft Systems Methodology

Abstract: Science, technology, engineering and mathematics (STEM) education is a globalized trend of equipping students to facilitate technological and scientific developments. Among STEM education, technology education (TE) plays a significant role in teaching applied knowledge and skills to create and add value to systems and products. In higher education, the learning effectiveness of the TE assisted by the immersive technologies is an active research area to enhance the teaching quality and learning performance. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…• Miller et al (2021), Wu et al (2021), and Hobbs and Holley (2022) each reported positive impacts of MR and VR on performance and engagement through immersive learning designs and curriculum integration.…”
Section: • Nadan Et Al (2011) Utilized Vr Technologies Like Cave Andmentioning
confidence: 99%
“…• Miller et al (2021), Wu et al (2021), and Hobbs and Holley (2022) each reported positive impacts of MR and VR on performance and engagement through immersive learning designs and curriculum integration.…”
Section: • Nadan Et Al (2011) Utilized Vr Technologies Like Cave Andmentioning
confidence: 99%
“…Several investigations have validated the use of immersive technology and the metaverse as the new constructivist teaching scenario in the post-pandemic era [46], given that it is an active methodology that promotes more excellent retention of information and meaningful learning [47], giving rise to a new pedagogical trend called immersive learning, which refers to the cognitive states that affect learning during activities within virtual environments designed for this purpose [48].…”
Section: Reference Main Objectivementioning
confidence: 99%
“…Additionally, SSM encourages stakeholders to envision desirable changes within their system by exploring alternative ways to effectively deal with multiple and often contradicting options. This principle fosters creativity and innovation while considering diverse stakeholder viewpoints (Wu et al, 2021). SSM uses a set of tools and techniques known as the "seven-stage model" (Strielkowski et al, 2023) (Fig.…”
Section: Introductionmentioning
confidence: 99%